Analysis of Planetary Closed Differential Motion in RV Reducer - Zhong Feng; Huaping Chen; Guanhua Feng; Xiaogang Liu; Jianjun Liu (Jixie chuandong)
The difference between the planetary differential mechanism and the planetary closed differential mechanism is analyzed by examples of planetary transmission mechanism. The evolution process of RV reducer from one tooth differential cycloid needle wheel reducer is analyzed，the concept that the crank shaft is a negative 1 tooth sun wheel in a tooth differential meshing drive is proposed and the transmission ratio equivalent calculation is carried out. The power flow diagram of RV reducer is equivalent，and the transmission power distribution ratio formula of each branch is obtained，and the essence of planetary closed differential motion of RV reducer is revealed. This theoretical analysis is instructive for the forward design of the RV reducer.